Histopathological Pattern of Difficult Childhood Nephrotic Syndrome in A Tertiary Care Centre, Bangladesh - Roy, Ranjit Ranjan; Rahman, Farhana; Arju, Jahanara; Sultana, Jakia; Chaki, Agomoni; Akter, Amina; Mamun, Abdullah Al; Jesmin, Tahmina; Huque, Syed Saimul; Begum, Afroza; Uddin, Golam Muin; Rahman, Md Habibur (Journal of Pediatric Nephrology, 2019)
Background The aim of this study was to know the spectrum of histopathology in children who underwent a renal biopsy for difficult NS in a tertiary care pediatric nephrology center. Method This prospective observational study took place in Pediatric Nephrology department of Bangabandhu Sheikh Mujib Medical University, Dhaka Bangladesh, from January 2011 to July 2018. Patients presented with difficult pattern of nephrotic syndrome and underwent renal biopsy were enrolled in this study. Results Total 140 patients were recruited in this study. Patients with SRNS & nephrotic syndrome with atypical presentation had renal biopsy ; a good number of atypical NS were SDNS. They were grouped into Group A: SRNS, Group B: SDNS, Group C:Nephrotic Syndrome with atypical presentation. Comparison among 3 groups were done. Regarding lab parameters, serum creatinine was raised in 40.6% patients in nephrotic syndrome with atypical presentation and 16.2%in SRNS. In patients with SDNS, MCD (51.3%) was the most common histological pattern followed by MesPGN (33.3%); whereas MesPGN was the commonest histological pattern in SRNS (56.8%) and atypical presentation (54.7%) followed by MCD and FSGS.Most of the patients response to immunosuppressive therapy. In SRNS partial response achieved in 18.9% and CKD developed in 16.2% cases. In comparison, nephrotic syndrome atypical presentation 10.9% patients achieved partial response and 7.8% developed CKD but these are not statistically significant. 5.4% patients of SRNS died. Conclusion Mesangioproliferative glomerulonephritis was the most common histopathological diagnosis in patients with SRNS & nephrotic syndrome atypical presentation in our population. MCD is predominant among SDNS.